Manifestation of the Upper Hubbard band in the 2D Hubbard model at low electron density: Низкоразмерные структуры - Kagan, M.Yu.; Val’kov, V.V.; Woelfle, P. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
We consider the 2D Hubbard model in the strong-coupling case (U >> W) and at low electron density (nd 2 > W and low electron density. Both poles produce nontrivial corrections to Landau Fermi-liquid picture already at low electron density but do not destroy it in 2D.